Effective Strategies in Managing Consumer Behavior - Sadiqin, Amin; Kurniawati, Aprilia Tri (CV. Proaksara Global Transeduka, 2024)
Marketing strategy encompasses a comprehensive range of tactics aimed at attaining a long-lasting competitive edge. Its ultimate objective revolves around achieving total customer satisfaction through the implementation of various marketing concepts, tips, and strategies. However, it is crucial to understand that true customer satisfaction lies not in providing what we assume they desire, but rather in delivering exactly what they want, precisely when and how they desire it. Consumer behavior, on the other hand, entails the entire process and activity of seeking, selecting, purchasing, utilizing, and evaluating products and services to fulfill one's needs and desires. This journey of buyers in making purchasing decisions can be broken down into five distinct phases: recognizing the need, conducting an information search, evaluating alternatives, making the purchase decision, and taking post-purchase actions.